2011
DOI: 10.1021/jm101417n
|View full text |Cite
|
Sign up to set email alerts
|

Analogues and Derivatives of Oncrasin-1, a Novel Inhibitor of the C-Terminal Domain of RNA Polymerase II and Their Antitumor Activities

Abstract: To optimize the antitumor activity of oncrasin-1, a small molecule RNA polymerase II inhibitor, we evaluated 69 oncrasin-1 analogues for their cytotoxic activity against normal human epithelial cells and K-Ras mutant tumor cells. About 40 of those compounds were as potent as or more potent than oncrasin-1 in tumor cells and had minimal cytotoxic effect on normal cells. Structure-activity relationship analysis revealed that most of the active compounds contained either a hydroxymethyl group or an aldehyde group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 43 publications
2
57
0
Order By: Relevance
“…Through chemical library screening on cells with or without a mutant KRAS gene [115] and lead compound optimization [118][119][120], we recently developed a novel compound designated oncrasin-72 (NSC743380) that is highly active [median growth inhibitory concentration (IC 50 ) between 10 nM and 1 μM] in vitro in 30 of 102 cancer cell lines tested [118,121], including many KRAS mutant cancer cell lines [115,119,121]. Mechanistic characterization revealed that NSC743380 and its analogs induced apoptosis in sensitive cancer cells [115,118,119], inhibited phosphorylation of the C-terminal domain of RNA Pol II [120,122], induced sustained JNK activation by inhibiting its dephosphorylation [119], induced reactive oxygen species (ROS) accumulation [117], inhibited STAT3 phosphorylation, and suppressed cyclin D1 expression [118], suggesting that NSC743380 modulates multiple cancer-related targets.…”
Section: Treatment Response In Ras Mutant Human Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through chemical library screening on cells with or without a mutant KRAS gene [115] and lead compound optimization [118][119][120], we recently developed a novel compound designated oncrasin-72 (NSC743380) that is highly active [median growth inhibitory concentration (IC 50 ) between 10 nM and 1 μM] in vitro in 30 of 102 cancer cell lines tested [118,121], including many KRAS mutant cancer cell lines [115,119,121]. Mechanistic characterization revealed that NSC743380 and its analogs induced apoptosis in sensitive cancer cells [115,118,119], inhibited phosphorylation of the C-terminal domain of RNA Pol II [120,122], induced sustained JNK activation by inhibiting its dephosphorylation [119], induced reactive oxygen species (ROS) accumulation [117], inhibited STAT3 phosphorylation, and suppressed cyclin D1 expression [118], suggesting that NSC743380 modulates multiple cancer-related targets.…”
Section: Treatment Response In Ras Mutant Human Cancer Cellsmentioning
confidence: 99%
“…Mechanistic characterization revealed that NSC743380 and its analogs induced apoptosis in sensitive cancer cells [115,118,119], inhibited phosphorylation of the C-terminal domain of RNA Pol II [120,122], induced sustained JNK activation by inhibiting its dephosphorylation [119], induced reactive oxygen species (ROS) accumulation [117], inhibited STAT3 phosphorylation, and suppressed cyclin D1 expression [118], suggesting that NSC743380 modulates multiple cancer-related targets. Blocking NSC743380-induced ROS generation with antioxidants dramatically abolished its apoptosis-inducing ability but had minimal effect on its inhibition of STAT3, suggesting that STAT3 inhibition is not caused by ROS production.…”
Section: Treatment Response In Ras Mutant Human Cancer Cellsmentioning
confidence: 99%
“…Our results have led to reports of the development of a group of novel anticancer agents called oncrasins. 13 In addition, in an in vitro study of the NCI-60 cancer cell line panel and other cancer cell lines, we demonstrated that structurally similar compounds elicited a similar anticancer spectrum in a subset of cancer cell lines, including KRAS -mutant cells. 2, 4, 5 Mechanistic characterization revealed that this group of anticancer agents triggered apoptosis by modulating subcellular localization of PKC-iota, 1, 6 disrupting mRNA processing machinery, 7 inhibiting JNK dephosphorylation, 2 inducing oxidative stress, 6, 8 and inhibiting STAT3 phosphorylation, 4, 5 suggesting that those agents modulate the functions of multiple cancer-related targets.…”
Section: Introductionmentioning
confidence: 70%
“…Our own study revealed that NSC-743380 tends to form dimers in solutions with water and loses activity, especially in low-pH conditions. 3 We hypothesized that the stability of NSC-743380 can be improved by protecting the hydroxyl group of NSC-743380 from dimer formation. To test this hypothesis, we synthesized and evaluated 5 ester derivatives of NSC-743380, and evaluated their spontaneous release of NSC-743380 in phosphate buffered saline.…”
Section: Introductionmentioning
confidence: 99%
“…1), a multi-targeted receptor tyrosine kinase inhibitor containing indolin-2-one moiety, was approved by the FDA for the treatment of advanced renal cell carcinoma (RCC) and gastrointestinal stromal tumors (GIST) [12]. Moreover, benzyl-1H-indole derivatives also possess prominent antitumor activity [13], such as a novel synthetic microtubule inhibitor D-24851 3 (Phase I/II, Fig. 1) [14] and oncrasin-1 4 (Fig.…”
Section: Introductionmentioning
confidence: 99%